Reinforcement Number of a Graph with respect to Half-Domination - G. Muhiuddin; N. Sridharan; D. Al-Kadi; S. Amutha; M. E. Elnair (Journal of Mathematics)
In this paper, we introduce the concept of reinforcement number with respect to half-domination and initiate a study on this parameter. Furthermore, we obtain various upper bounds for this parameter. AMS subject classification: 05C38, 05C40, 05C69.